Characterization of Cronobacter spp. isolated from food of plant origin and environmental samples collected from farms and from supermarkets in the Czech Republic - Vojkovska, Hana; Karpiskova, Renata; Orieskova, Maria; Drahovska, Hana (International journal of food microbiology, 2016)
The Cronobacter genus (previously known as Enterobacter sakazakii) comprises seven species (Cronobacter sakazakii, Cronobacter malonaticus, Cronobacter muytjensii, Cronobacter turicensis, Cronobacter dublinensis, Cronobacter universalis and Cronobacter condimenti)which cause serious infections in neonates and immunocompromised people.Most of the documented outbreaks of these bacteria have been associated with consumption of contaminated powdered infant formula. The plant environment is considered to be the natural habitat of these bacteria. Therefore, a total number of 563 samples of vegetables, fruit, water and environmental swabs were collected from local farms and supermarkets in the Czech Republic and investigated for the presence of Cronobacter spp. The obtained 45 isolates (8.0%) were further characterized by phenotyping (antimicrobial resistance, capsule and pigment production) and genotyping (fusA sequencing,MLST, PCR-serotyping) methods. Most of the Cronobacter isolates (42.2%) were identified as C. sakazakii, followed by C. turicensis (31.1%), C. dublinensis (22.2%), C. malonaticus (2.2%) and C. universalis (2.2%). The 25 identified sequence types, out of which 17 were unique for only one strain, indicated a high diversity of strains. C. sakazakii sequence type 4 (ST 4), which has been associated with many cases of meningitis, was isolated only in one case. A strong association of C. turicensis and C. dublinensis with the plant environment can be deduced from our results.
Keywords: Plants; Microbial Sensitivity Tests; Serotyping; novorozenec; Infant, Newborn; Infant; Humans; náhražky mateřského mléka; kojenec; Multilocus Sequence Typing; Agriculture; mikrobiální testy citlivosti; Genotype; lidé; antibakteriální látky; Cronobacter spp.; Vegetables; zelenina; Food Microbiology; Anti-Bacterial Agents; zemědělství; multilokusová sekvenční typizace; polymerázová řetězová reakce; Czech Republic; Cronobacter; Polymerase Chain Reaction; ovoce; Bacterial Typing Techniques; genotyp; Fruit; Infant Formula; Food; Česká republika; MLST; techniky typizace bakterií; potravinářská mikrobiologie